1954
DOI: 10.1136/bmj.1.4853.55
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Hyperinsulinism Due to Islet-cell Adenoma

Abstract: Spontaneous hyperinsulinism resulting from a tumour of the islets of Langerhans is not a common condition, and the diagnosis is easily overlooked. Failure in diagnosis usually results in the early death of the patient, while diagnosis followed by operative removal of the tumour cures the majority of patients.Nicholls (1902) first described an adenoma of the islet cells of the pancreas, but this was an incidental finding at necropsy and no clinical details of the case were recorded. Following the discovery of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1955
1955
1972
1972

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…abnormality, corresponding to these manifestations. Black et al (1954) reported a case developing a hemiplegia, and it seems that vascular insufficiency may be superimposed on the more diffuse pathological changes of hypoglycaemia described by Lawrence et al (1952), and resembling the findings in cerebral anoxia. In obscure cases of epilepsy of late onset when investigations have failed to reveal a cerebral neoplasm, the diagnosis of cortical atrophy or cerebral arteriosclerosis is sometimes too easily accepted.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…abnormality, corresponding to these manifestations. Black et al (1954) reported a case developing a hemiplegia, and it seems that vascular insufficiency may be superimposed on the more diffuse pathological changes of hypoglycaemia described by Lawrence et al (1952), and resembling the findings in cerebral anoxia. In obscure cases of epilepsy of late onset when investigations have failed to reveal a cerebral neoplasm, the diagnosis of cortical atrophy or cerebral arteriosclerosis is sometimes too easily accepted.…”
Section: Discussionsupporting
confidence: 53%
“…The clinical features corresponded to the now well-known picture of hyperinsulinism,and investigation In all the previously reported cases of adenomatosis of the islets the condition has been discovered either at necropsy or after subtotal resection of the pancreas occasioned by relapse of symptoms following previous removal of single adenomata. Many authors, including Black et al (1954) recently, stress the dark red or plum-coloured appearance of these neoplasms, and their firm consistency as compared with normal pancreatic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors, including Black et al (1954) recently, stress the dark red or plum-coloured appearance of these neoplasms, and their firm consistency as compared with normal pancreatic tissue.…”
mentioning
confidence: 99%
“…abnormalities and the blood sugar level (Bonnet and Malpertuy, 1955;Black et al, 1954;Solis and Vara Lopez, 1954;Hoefer, Guttman, and Sands, 1946). However, Bonnet and Malpertuy (1955), Gibbs and Murray (1954), Wyke (1952), and many other workers have also drawn attention to the lack of parallelism between the clinical state and the levels of blood sugar.…”
Section: Commentmentioning
confidence: 99%
“…(2) Because it has been often stated (Breidahl et al 1956;Black, Corbett, Hosford, and Turner, 1954;Crain and Thorn, 1949) that the electro-encephalogram (E.E.G.) is of little value in the diagnosis of this condition and this case shows that, properly applied, it may make a valuable contribution.…”
mentioning
confidence: 98%